Exploring the oasis of plant genomes: From genetic variations to function and beyond - Xu Han; Zhanxiang Zong; Weidong Ning; Yuting Zhang; Zengdong Tan; Yunhao Liu; Yukun Song; Qiyuan Long; Yuyan Xiang; Shaoping Lu; Xuan Yao; Hu Zhao; et al. (Molecular Plant, 2026)

Study on preparation and performance characteristics of solid waste-based open-pore mineralized filling material - Yao Lu; Shaoping Ren; Wei Lu; Guansheng Qi; Yongqiang Zhou; Changxiang Wang (Process Safety and Environmental Protection, 2026)

Modulation of the gut-skin axis by polysaccharides: Mechanisms and therapeutic potential in immune-related skin diseases - Chen Haiming; Liao Yijing; Tang Bin; Ma Xiaoyu; Li Hailun; Dong Meiting; Li Ziqing; Zheng Xuwei; Yang Yujie; Su Zuqing; Li Shaoping; Lu Chuanjian (Carbohydrate Polymers, 2025)

Subsurface structure of a buried Eratosthenian crater on the far-side of the Moon - Ling Zhang; Chunyang Zhao; Xintong Dong; Shaoping Lu; Yi Xu; Yuqi Qian; Shuo Han; Zhijun Huo; Rui Gao (Earth and Planetary Science Letters, 2025)

A review of green solvents for the extraction and separation of bioactive ingredients from natural products - Shaoping Ma; Changyong Cai; Qianwen Lu; Zhijian Tan (Food Chemistry, 2025)

Resilience-based complex system early design using dynamic Copula Bayesian network: Heave compensation hydraulic system design as a case study - Chao Zhang; Yaohui Lu; Rentong Chen; Shaoping Wang; Hongyan Dui; Yuwei Zhang; Yadong Zhang (Ocean Engineering, 2025)

Establishment and characterization of a novel cell line derived from spotted sea bass Lateolabrax maculatus and its susceptibilities to iridoviruses - Zhipeng Zhan; Xueqian Cao; Jie Su; Yangchi Cui; Yang Zheng; Pengli Xiao; Zhoutao Lu; Shaoping Weng; Changjun Guo; Jianguo He (Aquaculture, 2025)

Reproductive toxicity of bisphenol A and nitro-bisphenol A in male zebrafish at environmentally relevant concentrations - Chao Wang; Shuyi Zhang; Zijin Shao; Peijie Sun; Jiran Zhang; Shaoping Zhang; Jian Kong; Hong Zhi; Li Li; Mingshu Li; Jie Yu; Zhenming Liu; et al. (Science of The Total Environment, 2025)

Seismic Reflection Imaging Reveals Relict Subduction Zone of the Paleo-Pacific Plate in the Northeastern South China Sea - Zongdong Pan; Shaoping Lu; Hongfang Gao; Lun Li; Han Chen; Rui Gao; Qing He (Journal of Asian Earth Sciences, 2024)

Microseisms associated with the southwest summer monsoon recorded on the seafloor of South China Sea - Yulong Zhou; Fansheng Kong; Han Zhang; Zhangju Liu; Xiongwei Niu; Aiguo Ruan; Shaoping Lu; Jianke Fan; Pingchuan Tan; Xiaodong Wei; Weiwei Ding; Jiabiao Li (Earth and Planetary Science Letters, 2024)

The effect of pre-existing structures on the Cenozoic rifting processes: Insights from seismic reflection imaging of the northeastern south China sea - Zongdong Pan; Shaoping Lu; Hongfang Gao; Qing He; Han Chen; Xiao Ge (Journal of Structural Geology, 2024)

A Study on the Impact of Vertical Grid Parameter Perturbations in the Regional Ocean Modeling System - Lei Wang; Feng Zhang; Chongwei Zheng; Yaozhao Zhong; Tianxiu Lu; Shaoping Shang; Siyu Pu; Guodong Xia; Huafei Chen; Wei Leng (Journal of Marine Science and Engineering, 2024)
In this study, the Regional Ocean Modeling System (ROMS) is employed to construct a three-dimensional barotropic ocean model with a monodirectional upper boundary and homogeneous and steady wind covering the entire computation area. Eight perturbation experiments are designed to determine the vertical grid distribution difference with high resolution at the surface and bottom. Two types are considered in the model, including removing the Coriolis force (type 1) and employing a different Coriolis force (type 2). According to the experiments, the velocity of the current in type 1 yields uncertainty, and wind energy could penetrate the upper ocean and reach the abyss. The surface velocity in type 2 is fundamentally compatible with the empirical relationship constructed by Ekman, and the curved lines of the vertical distribution of horizontal currents nearly match. For type 1, the velocity is very strong from the sea surface to the bottom. When comparing type 1 and type 2 cases, the Coriolis force obstructs the wind energy transfer into the deep ocean. In addition, the European Centre for Medium-Range Weather Forecasts (ECMWF)’s global surface wind distribution indicates that the realistic ocean upper wind boundary is similar to the numerical experiment in the Pacific and Atlantic oceans, where the wind direction is along the latitude line at the equator. In order to make the experimental situation as close as possible to the real ocean, validation experiments are conducted in this study to consider the uncertainty in the current profile at the equator. The simulation results of type 1 differ significantly from the data obtained from the real ocean. This uncertainty may transfer the signal to higher latitudes, causing incorrect simulation results, especially in the critical region. Overall, this research not only makes discoveries in physical ocean theory but also guides predictive and forecasting techniques for ocean modeling.

Mutual-guided scale-aggregation denoising network for seismic noise attenuation - Tie Zhong; Zheng Cong; Xunqian Tong; Shiqi Dong; Shaoping Lu; Xintong Dong (Computers & Geosciences, 2024)

BnaPLDα1-BnaMPK6 Involved in NaCl-Mediated Overcoming of Self-Incompatibility in Brassica napus L. - Yuanyuan Li; WenXuan Zhang; Yong Yang; Xiaomei Liang; Shaoping Lu; Chaozhi Ma; Cheng Dai (Plant Science, 2024)

Detoxification and removal of heavy metal by an acid-tolerant microalgae, Graesiella sp. MA1 - Lu Zhang; Jin Wang; Rui Shao; Xin Chuai; Shaoping Wang; Zhengbo Yue (Journal of Water Process Engineering, 2024)

Origin of a high-velocity layer: Insights from seismic reflection imaging (South China Sea) - Qing He; Zongdong Pan; Shaoping Lu; Hongfang Gao; Han Chen; Rui Gao (Marine and Petroleum Geology, 2024)

Preliminary Results of the Seismicity Monitoring Experiment around the 2019 Mw5.4 Earthquake Epicenter in the Central South China Sea Basin - Wenfei Gong; Aiguo Ruan; Xiongwei Niu; Zhenjie Wang; Pingchuan Tan; Xiaodong Wei; Wei Wang; Zhengyi Tong; Liqun Cheng; Fansheng Kong; Shaoping Lu; Jianke Fan; et al. (Journal of Earth Science, 2024)

Lithospheric velocity structure of South China Sea basin from ocean bottom seismometer ambient noise tomography - Liqun Cheng; Yinxia Fang; Xiongwei Niu; Tingzi Li; Chongzhi Dong; Yanghui Zhao; Hao Hu; Fansheng Kong; Pingchuan Tan; Aiguo Ruan; Shaoping Lu; Jianke Fan; et al. (Tectonophysics, 2023)

MOF-derived LDH modified flame-retardant polyurethane sponge for high-performance oil-water separation: Interface engineering design based on bioinspiration - Junxiu Piao; Mingjie Lu; Jinyong Ren; Yaofei Wang; Tingting Feng; Yaxuan Wang; Chuanmei Jiao; Xilei Chen; Shaoping Kuang (Journal of Hazardous Materials, 2023)

Seismic Shot Gather Denoising by Using a Supervised-Deep-Learning Method with Weak Dependence on Real Noise Data: A Solution to the Lack of Real Noise Data - Xintong Dong; Jun Lin; Shaoping Lu; Xingguo Huang; Hongzhou Wang; Yue Li (Surveys in Geophysics, 2022)

Using hydro-climate elasticity estimator and geographical detector method to quantify the individual and interactive impacts on NDVI in oasis-desert ecotone - Jingjing Chang; Lu Gong; Fanjiang Zeng; Jie Xue; Donglei Mao; Yongxiang Cao; Guijin Mu; Shaoping Wang (Stochastic Environmental Research and Risk Assessment, 2022)

Rapid visual detection of Enterocytozoon hepatopenaei by recombinase polymerase amplification combined with lateral flow dipstick - Jianhu Pang; Caiyuan Zhao; Hualong Su; Zhongcheng Liu; Qiang Lu; Xinyi He; Shaoping Weng; Jianguo He (Frontiers in Marine Science, 2022)
Enterocytozoon hepatopenaei (EHP) is a high-impact pathogen in shrimp farming, causing huge economic losses to the global shrimp farming industry every year. However, current EHP detection methods are primarily based on the development of polymerase chain reaction (PCR) techniques that rely on sophisticated and expensive instruments. Consequently, a rapid, practical, and sensitive protocol for the detection of EHP is necessary. Recombinase polymerase amplification combined with a lateral flow dipstick (LFD-RPA) assay was developed using a pair of primers and nfo-probe targeting the conserved region of the spore wall protein gene. Under optimized reaction conditions, the LFD-RPA assay can detect 10 copies/μL of standard plasmid within 20 min at 40°C. Furthermore, the specificity of the LFD-RPA was also verified with other common pathogens of shrimp. Thirty-nine samples of Litopenaeus vannamei were collected in shrimp farms and detected using LFD-RPA and nested PCR. Thirty-two positive samples were detected by LFD-RPA. Compared with those of nested PCR, the diagnostic sensitivity and specificity of LFD-RPA were 100% and 100%, respectively. These results indicated the great application potential of the newly developed LFD-RPA assay for point-of-care diagnosis, epidemic surveillance, and epidemiological investigation of EHP.

Numerical Simulation of Cavitation and Damping Force Characteristics for a High-Speed Supercavitation Vehicle - Rui Lu; Guang Pan; Kun Tan; Shaoping Yin (Journal of Marine Science and Engineering, 2021)
In this study, an attempt has been made to investigate the supercavitation and hydrodynamic characteristics of high-speed vehicles. A homogeneous equilibrium flow model and a Schnerr–Sauer model based on the Reynolds-averaged Navier–Stokes method are used. Grid-independent inspection and comparison with experimental data in the literature have been carried out to verify the accuracy of numerical methods. The effect of the navigation speed and angle of attack on the cavitation morphology and dynamic characteristics has been investigated. It has been demonstrated that the angle of attack has a remarkable influence on the wet surface and hydrodynamic force, whereas navigation speed has little effect on the position force of the vehicle under the circumstance of no wet surface. The hydrodynamic force changes periodically with the swing of the vehicle, but its maximum is greater than that for the direct navigation state at the same attack angle. Moreover, the damping effect obviously affects the hydrodynamic force amplitude and movement trend.

ORF005L from infectious spleen and kidney necrosis virus is located in the inner mitochondrial membrane and induces apoptosis - Rui Wang; Yang Yi; Lihong Liu; Yanghong Lu; Shaoping Weng; Jianguo He; Xiaopeng Xu (Virus Genes, 2014)

Identification of the VP92R gene from infectious spleen and kidney necrosis virus - Xiaopeng Xu; Qingxia Lu; Rui Wang; Ting Lin; Shaoping Weng; Ling Lu; Zhongsheng Li; Xiaoqiang Yu; Junliang Tang; Jianguo He (Virus Genes, 2010)

Characterization of a membrane protein (VP001L) from infectious spleen and kidney necrosis virus (ISKNV) - Xiaopeng Xu; Jing Lu; Qingxia Lu; Hui Zhong; Shaoping Weng; Jianguo He (Virus Genes, 2008)